Modeling of Multifamily Residential Parking Use in King County, Washington. Issue 1 (January 2014) - Rowe, Daniel; Morse, Stephanie; Ratchford, Craig; Haas, Peter; Becker, Sofia
Multifamily residential buildings often provide too much parking, which can be an impediment to a wide range of community goals. An over-supply of parking can have deleterious effects on economic development, consumers, the community at large, and the environment. Despite a recent surge in research, a lack of consensus still exists on the factors that drive demand for parking in multifamily buildings across a variety of urban and suburban contexts. Although sociodemographic, housing, and built environment variables have all been shown to have an impact on residential parking and vehicle availability, their relative influence is a source of debate. This research identified independent variables to be tested in a regression analysis of 208 multifamily parking use studies conducted in King County, Washington, in 2012. Parking use was correlated to building characteristics as well as to the neighborhood in which the building resided. The final model derived from this regression analysis contained a goodness of fit with an R 2 value of 81.0% and incorporated seven variables: five pertained to the property or development characteristics and two to the built environment, specifically to access. The results of this study were intended for use by practitioners on an interactive website tool, the King County Multi-Family Residential Parking Calculator (www.rightsizeparking.org ), which condensed the research findings into a simple, map-based format, accessible to a wide variety of stakeholders.